Proposta de um método de avaliação do nível de utilização das práticas lean manufacturing: estudo de caso na APL do alumínio do sudoeste do Paraná - Vieira, Everton Luiz (2017)
Management techniques such as Lean Manufacturing are increasingly being used by companies, mostly in industries, aiming to increase efficiency and profitability in the face of the fierce industry competitiveness. However, informations about the practices and evaluation models of Lean are not always available for the companies. Considering that Lean is based on the waste elimination and on continuous improve seeking the Lean culture. Therefore, this dissertation outlines the proposition of a method to measure the degree of Lean practices at the aluminium APL in the southwest of Paraná, that does not own any Lean system formally structured. The presented method is based on studies of Saurin and Ferreira (2008), items of the regulation SAE J4000 and J4001, studies of Duran and Batochio (2003) and the house of Toyota System of Production where it was adapted a survey to raise informations about the uses of Lean practices at the companies that were studied, the practices were divided by principles and bases of the STP house. With the obtained results it was possible to identify that the aluminium APL companies uses only 13,63% of the 15 evaluated Lean practices. Finally the detailed analysis of the results highlighted improvements opportunities in terms of the Lean practices use in the aluminium APL companies.